Development and Calibration of a Three-Directional High-Energy Particle Detector for FY-3E Satellite - Guohong Shen; Xiaoxin Zhang; Jinhua Wang; Cong Huang; Jiawei Li; Shenyi Zhang; Xianguo Zhang; Yong Yang; Pengfei Zhang; Yueqiang Sun (Aerospace, 2023)
According to the characteristics of the LEO space particles radiation environment of China’s Fengyun No. 3 (FY-3) polar-orbiting meteorological satellites, in order to monitor the characteristics, and space–time distribution of charged particle radiation in the orbit space, it is proposed to install a three-directional high-energy particle detector (HEPD) in the three vertical orthogonal directions of FY-3E, so as to carry out the energy spectrum and flux observation of high-energy protons and electrons in the three directions of the satellite, namely, −X, +Y, and −Z. The on-orbit detection data acquired by these payloads can be used for space environment modeling and solar-terrestrial physics research, and provide data sources for operational space environment weather warning and forecasting. Through the ground accelerator calibration experiment and simulation analysis of the three-directional HEPDs developed in the flight model phase, the experimental results show that all the HEPDs’ measured values meet the requirements for technical indexes, such as the detection energy range (high-energy protons: 3–300 MeV; high-energy electrons: 0.15–5.7 MeV), energy span accuracy (<15%), flux accuracy (<15%), and sensitivity (<5% (ΔN/N)).